2014
DOI: 10.1080/14783363.2014.906107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ISO 9001 certification cancellation on business performance: a case study in Slovenian organisations

Abstract: This article highlights one of the actual ISO 9001 issues -a phenomenon of decrease in certification in Slovenia and worldwide as well. Our case study in Slovenia was focused on future functioning and financial performance of organisations having their ISO 9001 certificates cancelled (CCOs). The study was performed as a longitudinal survey covering more than 55% of the Slovenian certification market and taking a four-year period from 2009 to 2012. CCOs were analysed upon a study of the literature and previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…Among the studies that explore the motives of giving up QMS, we found diverse results pointing at different motivations such as the failure of audits (Marimon, Heras and Casadesús, 2009) or the lack of government support (Delmas, 2002;Casadesus, Giménez and Heras, 2001). There are also empirical studies that have analysed in detail the reasons for decertification (Alcalà, 2013;Kafel and Nowicki, 2014;Alič, 2014). However, decertification is not synonymous with giving up the QMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies that explore the motives of giving up QMS, we found diverse results pointing at different motivations such as the failure of audits (Marimon, Heras and Casadesús, 2009) or the lack of government support (Delmas, 2002;Casadesus, Giménez and Heras, 2001). There are also empirical studies that have analysed in detail the reasons for decertification (Alcalà, 2013;Kafel and Nowicki, 2014;Alič, 2014). However, decertification is not synonymous with giving up the QMS.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kafel and Nowicki (2014), after decertification studied companies still had a functioning QMS. The last paper by Alič (2014), analyses financial performance of Slovenian organizations that give up ISO 9001 certification. According to that research, the cancelation of ISO 9001 certificates is related to a decline in business performance of the organizations measured by ROA indicator.…”
Section: Introductionmentioning
confidence: 99%
“…According to a research conducted among Serbian companies [27] only quality tools for reviewing current condition (for decision making) have an important impact on financial performance measures. Some findings suggest that the cancelled ISO 9001 certificate could be understood as an early external signal indicating possible business problems in the organization [28]. According to research [29] quality managers consider expertise, knowledge and quality of preparation of the firm's staff for audit as the most important factors, while the external auditors put the expertise and professionalism of auditors in the first place.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Their number was rising on the global level all the years till 2011 and reached over 1.100.000 certificates worldwide (ISO, 2013). A slight decrease was noticed in the last year (on the global and European level), however in Slovenia the number of ISO 9001 certificates has been slightly falling since 2006 (Alič, 2014). There has already been some research performed pointing to stagnation of growth of the number of ISO 9001 certificates in some areas due to lower marketing attractiveness QM system certification (Sampaio et al, 2009;Boiral, 2012).…”
Section: The Role Of Qm Standards and Models In Businessmentioning
confidence: 99%